Bilobar agenesis of thyroid gland with hypertrophied isthmus (Journal of Institute of Medicine Nepal, 2011)
Bilobar agenesis of thyroid gland is a rare presentation of thyroid gland. Here we report an 18 years male presenting with history of midline swelling in the neck. Ultrasonography and CT neck revealed bilateral agenesis of thyroid gland with hypertrophied isthmus. Keywords: Bilobar agenesis of thyroid; Hypertrophied Isthmus DOI: http://dx.doi.org/10.3126/joim.v32i2.4947 Journal of Institute of Medicine, August, 2010; 32: 51-52